Genetic Diversity and Phylogeography of the Important Medical Herb, Cultivated Huang-Lian Populations, and the Wild Relatives Coptis Species in China - Wang, Xin; Liu, Xiao-Quang; Ko, Ya-Zhu; Jin, Xiao-Lei; Sun, Jia-Hui; Zhao, Zhen-Yu; Yuan, Qing-Jun; Chiang, Yu-Chung; Huang, Lu-Qi (Frontiers in Genetics, 2020)
Abstract Huang-lian (Coptis plants in China) are essential medicinal plants in China, C. chinensis var. chinensis and C. deltoidea have been domesticated and cultivated for 700 years. In this study, the genetic diversity patterns and biogeographical information of cultivated Huang-lian and their wild relatives Coptis species were assessed using three plastids DNA regions. A total of 186 individuals from twenty-seven populations representing two species of cultivated Huang-lian and four species of wild relatives were collected and analysed. Twenty-four haplotypes of six species were identified when three plastid spacers were combined. Historical biogeography inference revealed multiple dispersal events in the groups of cultivated Huang-lian and C. omeiensis. This evidence can infer that large initial population size and interbreeding with co-existing wild relatives in expanding new planting areas might be the main reason for maintaining the high genetic diversity of cultivated Huang-lian. Nevertheless, the multimodal curve of mismatch analysis and positive or negative differed among species and populations by neutrality tests indicated some groups of cultivated Huang-lian experienced genetic bottlenecks. Phylogeny analysis (NJ, MP, BI) showed that cultivated Huang-lian and C. omeiensis were clustered into a monophyletic group while C. chinensis var. brevisepala was paraphyletic, having earlier divergence time from C. chinensis var. chinensis (7.6 Ma) than C. omeiensis. Parsimony network demonstrated that C. deltoidea had more shared haplotypes with C. omeiensis than C. chinensis var. chinensis, and other haplotypes of C. deltoidea and C. omeiensis had less mutation steps than that of C. chinensis var. chinensis and C. omeiensis. This evidence suggests that C. omeiensis has a closer relationship with cultivated Huang-lian and might be a potential wild relative to C. deltoidea. The results reported here provide the baseline data for preserving genetic resources of Huang-lian and also evaluating the genetic impacts of long-term cultivation on medicinal plants, which could be instructive to future cultivation projects of traditional Chinese medicinal plants.